2015
DOI: 10.1158/1538-7445.am2015-3504
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3504: Synergism from combinations of monofunctional platinums with phytochemicals in human ovarian cancer cell lines

Abstract: Aims To apply combinations of monofunctional platinums with selected phytochemicals in human ovarian tumor models towards overcoming platinum resistance. Recently research has been directed at combinations of platinum drugs with tumor active phytochemicals towards a means of overcoming platinum resistance in ovarian cancer. In this study, two designed monofunctional planaramineplatinum(II) complexes, tris(8-hydroxyquinoline)monochloroplatinum(II) chloride (LH3) and tris(benzimidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…The vanilloid phytochemical 1 displays potent antineoplastic activity in multiple human cancers ,, and can improve the therapeutic efficacy of chemotherapeutic drugs and radiation therapy when used in combination. Despite such promising applications, the development of 1 as a clinically useful anticancer drug has been limited by its unpleasant side effects. The administration of 1 causes skin redness, hyperalgesia, nausea, intense tearing in the eyes, conjunctivitis, blepharospasm (sustained, forced, and involuntary closing of the eyelids), vomiting, abdominal pain, stomach cramps, bronchospasm, and burning diarrhea in patients. Clinical trials exploring the pain-relieving activity of 1 have shown that such side effects have resulted in patients discontinuing use of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vanilloid phytochemical 1 displays potent antineoplastic activity in multiple human cancers ,, and can improve the therapeutic efficacy of chemotherapeutic drugs and radiation therapy when used in combination. Despite such promising applications, the development of 1 as a clinically useful anticancer drug has been limited by its unpleasant side effects. The administration of 1 causes skin redness, hyperalgesia, nausea, intense tearing in the eyes, conjunctivitis, blepharospasm (sustained, forced, and involuntary closing of the eyelids), vomiting, abdominal pain, stomach cramps, bronchospasm, and burning diarrhea in patients. Clinical trials exploring the pain-relieving activity of 1 have shown that such side effects have resulted in patients discontinuing use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its pain-relieving activity, 1 exerts a wide variety of biological and pharmacological activities which may have important applications in the therapy of human diseases. Published data reveal that 1 and other capsaicinoids display strong antioxidant properties, promote energy metabolism, suppress fat accumulation, combat inflammation, and suppress the growth and progression of a diverse array of human cancers. The antineoplastic activity of 1 has been observed in leukemia, breast, lung, prostate, brain, gastrointestinal, and gynecological cancers. In several types of human cancers, capsaicin inhibits tumor invasion and metastasis to distant organs. , Apart from exerting direct growth-inhibitory activity toward human tumors, 1 sensitizes human cancer cells to the growth-suppressive effects of established chemotherapy drugs and radiotherapy. The multiple pharmacological activities of capsaicinoids have laid the foundation for detailed structure–activity-studies (SAR) focused on the development of potent, long-acting agonists and antagonists of the TRPV1 receptor with improved biological activity. Optical crystallography experiments conducted by Nelson and Dawson in 1923 deciphered the structure of 1 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although capsaicin and its cellular pathways relating the anti-cancer mechanism are not clearly understood, increased intracellular calcium, suppression of mitochondrial respiration, induction of calpain activity, formation of reactive oxygen species (ROS), inhibition of coenzyme Q, multiple mechanisms included inhibition of transcription factors such as nuclear factor-kB, STAT 3 (signal transducer and transcription activator) and p53 (tumor protein 53) are included in the relevant processes (9,(13)(14)(15). While the growth of human cancer cells is suppressed by capsaicin, the apoptic activity of cancer chemotherapy agents is supported by multiple mechanisms (9,13,16,17). The p-glycoprotein efflux transporters are inhibited by capsaicin in KB-C2 human endocervical adenocarcinoma cells, and the sensitization of cells to apoptosis and an increase in vinblastine concentration in the cellular microenvironment occurs as a result of treatment of KB-C2 cells with an antimicrotubule drug in the presence of capsaicin (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cross resistance and severe side effects of platinum drugs, such as nephrotoxicity, have limited their clinical application. In the past years, successful approaches have been employed to solve these drawbacks, combining platinum-based drugs with some other active pharmacophore so that a synergic action can be obtained [6]. Oxadiazole and triazole have been recently used for complexation of metal such as copper, nickel [7], palladium [8] and platinum [9]; 1,2,4-oxadiazoles have been widely studied for their chemistry [10][11][12], these heterocycles have gained attention for their pharmaceutical properties, and additionally, the presence of the fluorinated moiety opens the way to new fluorine-induced activity with respect to corresponding non-fluorinated systems [13][14][15][16] and application in materials [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%